PRINTMAKING AS A SOCIAL REPRESENTATION OF A CAT ABANDONMENT AT SALMAN ITB MOSQUE - Nur Azizah Mulyana, Shafira
The creation of living things consisting of humans, plants, animals, and the environment forms an ecological system called an ecosystem. Ecosystem works on its own and have regularities that impact one another so that it can maintain a balance in it. Cats are one of the animals that are familiar to humans. Its existence has helped human life since the early practices of agriculture 10,000 to 12,000 years ago. Until now, cats that have been domesticated by humans, their existence has turned into a friend and companion. Domestic cats can be found in all places on this world, but for public spaces such as Salman ITB Mosque, their presence can damage the balance of the ecosystem due to the increasing number of cat populations. The presence of cats in Indonesia can be found easily and the increase in the cat population has an impact on the environment of Salman ITB Mosque such as air pollution, disruption of human activities, and dirty environment. This happens because many cats are abandoned by humans at that location continuously. The case of cat abandonment at the Salman ITB Mosque is a serious problem in handling the cat population because it will reach overpopulation if not resolved. The point of this problem lies in the social problem of ignorance about the principles of cat welfare. So it takes an insight so that the relationship between humans and cats is maintained in the balance of the ecosystem. Departing from this idea, printmaking becomes an artistic medium and a solution to represent social issues. Through an approach to art as a representation, it can display an idea that has meaning behind it. This is reflected in the visualization of cases of cat abandonment at the Salman ITB Mosque and this final project is an opportunity to raise the issue of cat abandonment so that the opportunities provided can promote the principle of cat welfare in fine arts. Through works of art, it can be a medium that can be interpreted about the meaning in it.